A conceptual approach to the quality of the pre-investment stage - Aguilera García, Luis Alexis; Lao León, Yosvani Orlando; Sánchez Machado, Inocencio Raúl; Ledesma Martínez, Zulma María (Revista Venezolana de Gerencia, 2021)
The objective of the article is to propose a conceptual approach to the quality of the pre-investment stage, given the dispersion of criteria identified in this issue. The different perspectives and trends of the quality of the pre-investment stage, which constitutes the initial stage of the projects, were analyzed through the use of theoretical methods such as: analysis-synthesis, inductive-deductive and structural systemic under a bibliometric approach. Scientific publications were consulted on the Web of Science, Dimensions, Scielo and Redalyc, whose analysis allowed us to recognize the growing interest in the subject during 2020 and the prominence of the scientific journal Venezuelan of Management in its topic. As the main result, a conceptual approximation of the quality of the pre-investment stage is proposed that contains the variables: compliance with quality characteristics, social responsibility, satisfaction of the interested parties, costs, deadlines and reliability; resulting from the correlation analysis of the most used keywords in the identified definitions. This result may constitute the theoretical basis for the design of indicators and methodologies for the evaluation and improvement of the quality of the pre-investment stage.